O20-5 Psychological health and wellbeing in australian gulf war veterans, 20 years after deployment. (1st September 2016) - Kelsall, Helen; Ikin, Jillian; McKenzie, Dean; Gwini, Stella; Forbes, Andrew; Wright, Breanna; Sim, Malcolm
Abstract : Background: Ten years after the 1990–1991 Gulf War, Australian veterans were found to have significantly poorer psychological health and physical and mental wellbeing, compared to a military comparison group. Approximately 20 years after the Gulf War, the psychological health and wellbeing of the cohort was re-assessed. Methods: In a baseline study (2000–2002) and at follow up (2011–2012) the Composite International Diagnostic Interview (CIDI) was used to assess the presence of DSM-IV 12 month psychological disorders. Structured self-report instruments included the Short-Form 12 Health Survey, General Health Questionnaire-12, Patient Health Questionnaire-9, Posttraumatic Stress Disorder Checklist, Demoralisation Scale and Connor Davidson-Resilience Scale. Results: The risk of PTSD and alcohol disorder in Gulf War veterans (veterans) at follow up was approximately twice that in the comparison group (PTSD adj relative risk (RR) 2.37; 95% CI: 1.37–4.09; alcohol adj RR 1.93; 1.10–3.38). Since baseline, the risk of 12 month PTSD in veterans had significantly increased (adj RR 1.96; 1.29–2.97), in contrast the risk in the comparison group had remained relatively stable, and there was no significant difference between groups. Veterans were not at significantly excess risk of major depression at follow up, although they reported more severe depressive symptoms. Other DSM-IV psychological disorders were infrequent in both study groups. Veterans reported significantly poorer physical and mental wellbeing than the comparison group, and had higher levels of demoralisation but were equally resilient. Conclusions: Our findings highlight the 20 year longer-term psychological health and wellbeing of a Gulf War veteran cohort, indicating that psychological morbidity and poorer physical and mental wellbeing remain increased in veterans relative to a military comparison group. Effective strategies are needed to continue to identify and manage existing chronic conditions including psychological conditions and to prevent future cases.